1990
DOI: 10.1152/ajpregu.1990.258.4.r1084
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration increases the density of C receptors for ANF on rat glomerular membranes

Abstract: The present study determined the presence of two types of binding sites for atrial natriuretic factor (ANF), the B and C receptor, on rat glomerular membranes. The effect of short-term salt loading and dehydration on these two receptor populations was investigated consecutively. Salt-loaded rats did not show significant changes in plasma ANF concentrations or in the number of ANF binding sites. Water-deprived rats presented significantly lower plasma ANF concentrations (22.0 +/- 1.9 vs. 34.4 +/- 3.8 fmol/ml, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…Unfortunately, in our study, the plasma ANP levels in the fetal and pregnant rats were not significantly modified by a high-salt diet, suggesting that the amount of salt intake with saline solution does not interfere with ANP secretion. This result is in agreement with those of several investigations which showed that a high-salt diet did not modify the release of ANP in the adult rat (15,16,22,23) the pregnant rat (5,35). Previous studies have shown that the blood volume expansion is the physiological stimulus of ANP secretion by increasing atrial distension in the adult rat (36,37) and the fetal rat (38).…”
Section: European Journal Of Endocrinology (2000) 142supporting
confidence: 92%
See 3 more Smart Citations
“…Unfortunately, in our study, the plasma ANP levels in the fetal and pregnant rats were not significantly modified by a high-salt diet, suggesting that the amount of salt intake with saline solution does not interfere with ANP secretion. This result is in agreement with those of several investigations which showed that a high-salt diet did not modify the release of ANP in the adult rat (15,16,22,23) the pregnant rat (5,35). Previous studies have shown that the blood volume expansion is the physiological stimulus of ANP secretion by increasing atrial distension in the adult rat (36,37) and the fetal rat (38).…”
Section: European Journal Of Endocrinology (2000) 142supporting
confidence: 92%
“…The density of ANPb receptors was assessed with rANP in the presence of an excess of cANP (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (0.1 mmol/l; Peninsula), a truncated ANP peptide which binds selectively to ANPc receptors. The density of ANPc receptors was obtained by subtracting the number of ANPb receptors from the total receptor population.…”
Section: Binding Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, many studies in rats have shown that dehydration enhances plasma VP levels (34,35) as well as hypothalamic VP gene expression (34,36). Dehydration also causes a rise in plasma aldosterone levels (37), a fall in plasma ANP concentrations (38,39) and an increase in ANP-C receptor density in kidneys (38). It is not known if perinatal maternal malnutrition alters these homeostatic responses to dehydration.…”
Section: Introductionmentioning
confidence: 99%